The individual and joint effects of process control and process-based rewards on new product performance and job satisfaction - Pilar Carbonell; Ana I. Rodríguez-Escudero (BRQ Business Research Quarterly, 2016)
Summary An important issue facing innovation managers is how to exercise adequate managerial control over new product development (NPD) teams in order to ensure that project goals are met. The current study advances research on this subject matter by analyzing the individual and joint effects of process control and process-based rewards on job satisfaction and four measures of new product performance. Findings from our study reveal that process control and process-based rewards can have either positive or negative effects depending on the type of performance outcome considered. Thus, process control is beneficial to new product quality but detrimental to adherence to budget, adherence to schedule, and team's job satisfaction. Interestingly, our results suggest opposite effects for process-based rewards. In terms of their joint effects, results suggest that firms should only combine process control and process-based rewards when their goal is to develop new products with high quality."
Keywords: 650; New product development; Process control; Process-based rewards; Job satisfaction; New product performance